ELASTIC-PLASTIC ANNULAR DISK WITH VARIABLE THICKNESS SUBJECTED TO EXTERNAL-PRESSURE - GUVEN, U (SPRINGER-VERLAG WIEN, 1992)
The plane state of stress in an elastic-plastic annular disk with variable thickness under external pressure is studied. The thickness h is assumed to vary along the radius in the form h = h0(r/b)-n. The analysis is based on Tresca's yield condition, its associated flow rule and linear strain hardening.
Keywords: Mechanics